Income Smoothing Use Financing Loss Provision In Indonesia And Malaysia’s Islamic Banks - Fadhilah Hanum Lubis; Sigid Eko Pramono; Saiful Anwar (International Journal of Science, Technology & Management, 2021)
Rapid development of Islamic banks leads to the requirement to compete in order to show the best performance. Performance assessment can be seen from the profit information. Income smoothing through the use of Financing Loss Provision (FLP) is one method that can be applied in Islamic banking in an attempt to get income based on their goals. This research aims to investigate income smoothing practice by using FLP at both Indonesia and Malaysia’s Islamic banks by applying mixed-method approach. In this regard, quantitive method was used to measure panel regression by using Eviews in order to analyze income smoothing practice through FLP in both Indonesia and Malaysia than qualitative method was used through interviews with practitioners and sharia supervisors in Indonesia to get the data about the practice. The data in this research were taken from 11 Islamic banks in Indonesia and 19 Islamic banks in Malysia from 2011 to 2016. The results of the research reveal that Islamic banks in both Indonesia and Malaysia apply income smoothing by using FLP. The findings imply that Earning Before Taxes and Provision (EBTP) has significant positive effect on FLP. Moreover, the results of interviews indicate that Islamic banks in Indonesia do not apply income smoothing. However, there is an indication that they will lead to this condition. Therefore, it is suggested that the regulators will supervise the application of FLP by developing the investigation of this account in financial statement of the Islamic banks.